Exploration and Characterization of High-Efficiency Phosphate-Solubilizing Bacteria Isolates from Chickpea Rhizospheric Soil - Kumar, Vikash; Chourasia, Hirendra Kumar; Rajani, Kumari; Kumar, Ravi Ranjan (International Journal of Bio-resource and Stress Management, 2024)
The study was conducted during April, 2021 to June, 2022 to study the isolation and identification of high effective strains of phosphate solubilizing bacteria and evaluation the ability to solubilize tricalcium phosphate in vitro. Microorganisms that live in soil are actively involved in the carbon, nitrogen, sulphur, and phosphorus cycles in nature, enabling them to maintain ecological balance. Phosphate-solubilizing microbes are used as agricultural biofertilizers and play an essential role in plant nutrition by enhancing phosphate uptake. Phosphate is one of the most important macronutrients necessary for the growth and development of plants. Numerous microorganisms present in the rhizosphere solubilize insoluble phosphorus, making it readily available to plants. Fourteen phosphate-solubilizing bacterial colonies were identified on Pikovskaya’s agar medium, containing insoluble tricalcium phosphate (TCP) from rhizospheric soil. Among them, eight colonies showing clear halo zones around the microbial growth were considered as phosphate-solubilizing. All isolates showing the highest phosphate solubilization index (PSI), ranging from 2.8 to 4.03, were selected for further qualitative and quantitative studies. Out of these eight potent isolates, two strains showed the maximum PSI: V7 (4.03) and V8 (3.85) in agar plates, along with a high production of soluble phosphate, measuring 448.03 and 441.43 mg l-1, and a greater reduction in pH in the broth culture. The morphological, biochemical, and molecular identification of V7 and V8 strains revealed them to belong the Acinetobacter and Paenibacillus genera, respectively, and were phylogenetically close to Acinetobacter baumannii and Paenibacillus lautus species.